Knowledge, attitudes and risk perception surrounding blood transfusion in Trinidad and Tobago. (15th May 2018) - Charles, K. S.; Metivier, K. S.; Sammy, S.; Labban, M.; Rudder, M.; Singh, S.; Reginald, A.; Ramoutar, S.; Legall, G.; Pooransingh, S.; Chantry, A. D.
Abstract : Background and objectives: Trinidad and Tobago is a developing country with a hospital‐based, replacement blood donation system, low annual donation rate and high frequency of donor transfusion transmissible infections. Previous studies suggest a need for more information to improve total donations and encourage conversion to voluntary non‐remunerated blood donation. The aim of this study was to investigate public knowledge and perceptions about receiving blood to derive information for designing a safe blood donation campaign. Materials and methods: A cross‐sectional, questionnaire‐based survey was administered to a non‐randomly selected sample of adults at seven health centres. Participants were surveyed for demographics, knowledge of the local transfusion service, confidence in safety checks and attitudes to blood receipt. Results: Of 400 respondents, a substantial proportion (38·2%) was unaware of inadequate blood bank stock. Only 18·4% correctly identified the method of blood donor recruitment in the country. Only 1·2% of participants were able to identify all from a list of six scenarios, in which blood is transfused. Although 86% would accept transfusion, most (84%) of these had concerns about acquiring infections and hospital‐related activities. Young persons and females had higher risk perception ( P  =   0·026 and P  =   0·041). There was a positive association between confidence in the safety of blood donation processes and willingness to accept transfusion. Conclusion: A blood donor education programme should include all processes from donor recruitment to component administration to reduce the perceived risk of receiving blood in Trinidad and Tobago.